FROM BORDER AS A METHOD OF CAPITAL TO BORDERSCAPE AS A METHOD FOR A GEOGRAPHICAL OPPOSITION TO CAPITALISM - Chiara Brambilla (Bollettino della Società Geografica Italiana, 2019)
This article proposes a conceptual shift from political borders – essentially State borders in Modern times – as a structuring element of the unevenly developed landscape of the geography of capitalism, or, as a method of capital to «borderscapes» as a method for a geographical opposition to capitalism. Specifically, the article discusses the potential of a critical rethinking of the concepts of «border» and «landscape» by mobilizing the borderscape notion to cope with the contradictions of capitalism and to search for strategies able to face them at both theoretical and practical level. If capitalism has always been a fundamentally geographical project, as a number of scholars have argued, it seems necessary to think of a geographical alternative to it. Such an alternative cannot help but question some themes in the heart of geographical knowledge – in this article the themes of borders and landscape – inspiring a new (geo)political imagination for practicing a geographical opposition to capitalism.